Strategies for long-term monitoring of tide gauges using GPS - Teferle, Felix Norman (2003)
Changes in mean sea (MSL) level recorded relative to tide gauge benchmarks (TGBM) are corrupted by vertical land movements. Accurate estimates of changes in absolute sea level, require these MSL records to be corrected for ground level changes at tide gauge sites. For more than a decade, the Global Positioning System (GPS) has been used to determine positions of TGBMs and to monitor their position changes, i.e. station velocities, over time in the International Terrestrial Reference System (ITRS). This was initially carried out by episodic GPS campaigns and later on by continuous GPS (CGPS) or a combination of both.